2013
DOI: 10.1371/journal.pone.0064266
|View full text |Cite
|
Sign up to set email alerts
|

ROS-Dependent Mitochondria Molecular Mechanisms Underlying Antitumor Activity of Pleurotus abalonus Acidic Polysaccharides in Human Breast Cancer MCF-7 Cells

Abstract: BackgroundA greater reduction in cancer risk associated with mushroom diet rich in fungus polysaccharides is generally accepted. Meanwhile, edible Pleurotus abalonus as a member of Abalone mushroom family is a popular nutritional supplement that purportedly prevents cancer occurrence. However, these anecdotal claims are supported by limited studies describing tumor-inhibitory responses to the promising polysaccharides, and the molecular mechanisms underlying these properties have not yet been elucidated.Method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
34
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 68 publications
(36 citation statements)
references
References 43 publications
2
34
0
Order By: Relevance
“…The capability of anticancer drugs to induce the cellular apoptosis of cancer cells is an important property of cancer treatment (23,24). We observed a time-dependent apoptotic pattern with HF exposure that was similar between MCF-7 and MDA-MB-231 ( Fig.…”
Section: Discussionmentioning
confidence: 61%
“…The capability of anticancer drugs to induce the cellular apoptosis of cancer cells is an important property of cancer treatment (23,24). We observed a time-dependent apoptotic pattern with HF exposure that was similar between MCF-7 and MDA-MB-231 ( Fig.…”
Section: Discussionmentioning
confidence: 61%
“…For instance, Fomitopsis pinicola chloroform extract induced SW-480 cell apoptosis by increasing ROS accumulation [18]. Acidic PAP-3 (a polysaccharide) has also been shown to exert anti-cancer effects through the ROS-mediated mitochondrial apoptotic pathway [19]. In this study, we examined the pro-apoptotic effects of M. horridula extract and the role of ROS.…”
Section: Introductionmentioning
confidence: 99%
“…Polysaccharides from herb plants especially mushroom have been proven to be effective anti-tumor compounds with no toxicity (Shi et al, 2013;Giavasis, 2014;Ning et al, 2014). It has been reported that GLP exert strong anti-tumor effect when the molecular weight was larger than 1×10 4 (Liu et al, 2010).…”
Section: Discussionmentioning
confidence: 99%